Does microfinance reduce rural poverty? Evidence based on household panel data from Northern Ethiopia - Berhane, Guush; Gardebroek, Cornelis (Wiley, 2011)
Evidence on the long‐term impacts of microfinance credit is scarce. We use a unique four‐round panel dataset on farm households in northern Ethiopia that had access to microfinance, observed on two key poverty indicators: household consumption and housing improvements. Fixed‐effects and random trend models are used to reduce potential selection biases due to time‐invariant unobserved heterogeneity and individual trends therein. Results show that borrowing indeed causally increased consumption and housing improvements. A flexible specification that takes into account repeated borrowings also suggests that borrowing has cumulative long‐term effects on these outcomes, implying that short‐term impact estimates may underestimate credit effects.